Experimental study on transient thermal characteristics of stagger-arranged lithium-ion battery pack with air cooling strategy - Yu, Xiaoling; Lu, Zhao; Zhang, Liyu; Wei, Lichuan; Cui, Xin; Jin, Liwen (International journal of heat and mass transfer, 2019)
•Heat generation behavior of battery with Li(NixCoyAlz)O2 cathode is obtained by ARC.•Maximum temperature and temperature difference in battery pack can be maintained properly by natural cooling.•Forced air cooling strategy with longitudinal airflow significantly reduces temperature rise in battery pack.•Air cooling with flow velocity of 0.8 m⋅s−1 is recommended for achieving appropriate DOD of 84.2%. The thermal characteristics of lithium-ion battery affect significantly charging/discharging performance, cycle life and safety of electric vehicles (EVs) battery packs. In this study, a stagger-arranged battery pack consisting of three battery modules was developed to explore its transient thermal characteristics in charging/discharging process under the two cooling strategies, i.e., natural cooling and forced air cooling. The investigation of heat generation behavior of the battery with Li(NixCoyAlz)O2 cathode showed that the heat generation rate of the battery remains almost unchanged along the main discharging process, while a rapid increase in heat production is detected at the end of discharging. It was found that the maximum temperature and temperature difference in the battery pack subject to a moderate charging/discharging rate, e.g., 0.5 C, can be maintained within the desirable ranges by natural cooling. The forced air cooling strategy employing longitudinal airflow remarkably improves the battery’s transient thermal characteristics with achieving the depth of discharge (DOD) up to 84.2%, which is capable to prolong the battery pack’s cycle life to a large extent. Lastly, the appropriate air supply velocity of 0.8 m⋅s−1 is recommended for the proposed battery pack subject to a higher discharging rate, e.g., 1 C, from the viewpoint of cooling effectiveness.